2016
DOI: 10.1089/tmj.2016.0001
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Serious Games in Psychotherapy: An Inquiry into the Stance of Therapists and Patients

Abstract: The application of serious games is conceivable for patients and therapists, especially as a complementary element to traditional face-to-face psychotherapy. Acceptance is strongly related to therapeutic context. Only a small number of therapists and patients agree on the possibility of using a serious game instead of face-to-face therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 26 publications
3
28
0
4
Order By: Relevance
“…Future reviews could thus address both questions left open in this scoping review and compare study findings on acceptability of e-mental health between different groups of adopters, such as patients and clinicians [57] or laypersons and health professionals. For instance, Carper et al [33] showed rather negative attitudes toward e-mental health treatments among help-seeking persons, whereas surveyed health professionals tended to report neutral views.…”
Section: Discussionmentioning
confidence: 99%
“…Future reviews could thus address both questions left open in this scoping review and compare study findings on acceptability of e-mental health between different groups of adopters, such as patients and clinicians [57] or laypersons and health professionals. For instance, Carper et al [33] showed rather negative attitudes toward e-mental health treatments among help-seeking persons, whereas surveyed health professionals tended to report neutral views.…”
Section: Discussionmentioning
confidence: 99%
“…Keeping this in mind, many computer games developed to address the interest and necessity of autism children, since the games happened to be an attractive tool for intervention of children with special needs [8], [12]. The application of serious games is as a complementary element to traditional face-to-face psychotherapy [19]. Specialized games have developed over the recent years and there are many researchers are contributing for the development of educational and therapeutic games for the aid of special children.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, various interventions use electronic games (EG) in health and mental health, in a variety of diagnoses and therapeutic objectives [68,69].…”
Section: Why a Game?mentioning
confidence: 99%